2010
DOI: 10.1017/s1355617710000056
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia in Alzheimer’s disease: The role of impairment levels in assessment of insight across domains

Abstract: Impaired insight for deficits (anosognosia) is common in Alzheimer's disease (AD). However, it has not yet been determined clearly (a) whether different methods for assessing insight are comparable, and (b) whether anosognosia affects different domains to different degrees (domain-specificity). Impaired insight was investigated in 32 patients with AD, who were each accompanied by a caregiver. Anosognosia was assessed by a global clinical rating, questionnaire discrepancies (patient vs. caregiver) covering diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
27

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 43 publications
7
81
0
27
Order By: Relevance
“…It is important to note that individuals with MCI also have SCI (self-or informant-reported) as part of MCI's diagnostic criteria (Albert et al, 2011). However, self-awareness of cognitive impairment is highly variable in AD, including in its early stages (Leicht, Berwig, & Gertz, 2010;Orfei et al, 2010); therefore, individuals with AD in the included studies did not necessarily have SCI or had varying levels of SCI depending on study instrumentation. For the purposes of this review, inclusion of MCI or AD groups was used as an additional point of comparison with SCI groups (individuals with no objectively measured cognitive impairment).…”
Section: Results Of Reviewed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that individuals with MCI also have SCI (self-or informant-reported) as part of MCI's diagnostic criteria (Albert et al, 2011). However, self-awareness of cognitive impairment is highly variable in AD, including in its early stages (Leicht, Berwig, & Gertz, 2010;Orfei et al, 2010); therefore, individuals with AD in the included studies did not necessarily have SCI or had varying levels of SCI depending on study instrumentation. For the purposes of this review, inclusion of MCI or AD groups was used as an additional point of comparison with SCI groups (individuals with no objectively measured cognitive impairment).…”
Section: Results Of Reviewed Studiesmentioning
confidence: 99%
“…Therefore, it is important for future research to consider the meaning of self-versus informant-reported SCI as it relates to a potential preclinical AD indicator versus a component of affective symptomatology. It has been shown that there is variability in awareness of cognitive impairment among individuals at similar AD stages (i.e., mild to moderate impairment; Leicht et al, 2010;Orfei et al, 2010;Ownsworth, Clare, & Morris, 2006). Among individuals with MCI, self-reports of cognitive problems may relate more to affective symptoms, whereas informant reports may more reliably indicate objective cognitive decline (Edmonds et al, 2014).…”
Section: Sci Measurementmentioning
confidence: 99%
“…La prevalencia en la EA, oscila entre el 15 y el 68% y está estrechamente relacionada con la gravedad de la demencia [9][10][11] . No obstante, algunos autores han evidenciado discordancias entre el grado de anosognosia y la puntuación del Mini-Mental State Examination (MMSE) [9][10][11] .…”
Section: Pacientes Y Métodounclassified
“…No obstante, algunos autores han evidenciado discordancias entre el grado de anosognosia y la puntuación del Mini-Mental State Examination (MMSE) [9][10][11] . Debe mencionarse también, que la metodología utilizada para evaluar la presencia de anosognosia es muy diversa [12][13] .…”
Section: Pacientes Y Métodounclassified
See 1 more Smart Citation